Role of Sociolinguistics in Shaping Students’ Language Use in Multilingual Classrooms - Ida Bagus Nyoman Mantra; Wayan Maba; Ida Ayu Made Sri Widiastuti (International Journal of Multidisciplinary Approach Research and Science, 2025)
With an emphasis on how social and cultural elements impact communication, identity, and interaction, this study investigates how sociolinguistics shapes students' language use in multilingual classrooms. Students frequently switch between local, national, and international languages like English in multilingual educational settings, leading to intricate linguistic patterns. Using a qualitative design, the study examined how sociolinguistic dynamics emerge through teacher and student interviews and classroom observations in regular learning interactions. The results show that various factors, including peer pressure, instructors' language preferences, and the sociocultural status of particular languages, influence how students use language. Interviews revealed, for example, that students frequently transition between Indonesian, English, and their native tongues based on the situation and the person speaking to them. Teachers also purposefully employed sociolinguistic techniques like translanguaging to establish connections and guarantee understanding. In addition to facilitating communication, these activities helped students develop their social identities. The findings highlight how crucial sociolinguistic understanding is to creating welcoming classrooms that celebrate linguistic variety. According to findings, incorporating sociolinguistic perspectives into teaching methods can improve language acquisition, advance linguistic equity, and fortify students' multilingual proficiency.